Lady Justice or the golden calf? The “China factor” in Hong Kong’s legal system - Lai, Yan-ho (Emerald, 2019)
Despite the preservation of “One Country, Two Systems” for 50 years under the Sino-British Joint Declaration and Basic Law, changes are palpable due to the emergence of a real contest between liberal and pro-China actors in the legal profession and the legal environment in Hong Kong. After celebrating the twentieth anniversary of Hong Kong’s sovereignty transfer from Britain to China, it is valuable to study how the sovereign power influence the rule of law in its semiautonomous city by non-legal measures. This paper aims to offer a preliminary research on China’s political economic strategy, which is regarded as the “China factor”, in the legal system of Hong Kong, and its political, economic and legal-cultural impacts on the rule of law. This paper argues that China exerts its influence over the legal system of Hong Kong in four domains, including ideology, political elections, legal organization and cross-border political economy. Based on media research and content analysis over published materials of various legal associations and institutions, it is found that China attempts to consolidate its control in Hong Kong by producing alternative legal ideology and discourse of the rule of law and by co-opting the legal profession under China’s united front strategy. While there are liberal lawyers and legal scholars vocally engaging in defense of human rights and the rule of law in Hong Kong, a network of legal profession promoting socialist and authoritarian legal values has become prominent. Hong Kong’s legal culture will continue to be shaped in accordance with authoritarian characteristics and will adversely affect developing the rule of law in this international city. This paper contributes to the study of China’s influence over the legal profession of Hong Kong and in general Hong Kong’s jurisdiction by offering an example to the international community that contributes towards understanding how China adopts different strategies to expand political significance beyond its border.